User‐stakeholders' responsiveness: A necessary input for achieving in e‐governance transformation in developing countries. Issue 6 (18th July 2019) - Ngonzi, Tibuhinda; Sewchurran, Kosheek
Abstract: e‐Government is a social innovation phenomenon in the contemporary times, with extensive promises for social livelihood progress in developing counties. e‐Government has opened up potentials and opportunities for the operationalization of information and communication technologies (ICTs) for human development goals in the socioeconomic fields. e‐Government has unveiled political playgrounds for the citizens such as the Diasporas, who can participate in their home countries political processes through electronic voting for instance. e‐Government is a tool for the realization and strengthening of good governance processes. With such relevance in the background, there is always a gap for contribution in that context of technology and society relationships, through investigation of areas for implementation, improvement, or effective practicing of e‐government. In the implementation of e‐government, Tanzania is said to be evolving through the digital presence–interaction–transaction–transformation stages of e‐government maturity models (eGMMs). We are of the opinion that transformation for e‐government cannot be achieved in the pragmatics of eGMMs framework. We suggest the adoption of information systems project framework (ISPF) to enhance focusing on "user‐stakeholders" as strategic components for e‐governance effectiveness towards transformation, and that the responsiveness of user‐stakeholders at different levels of e‐government operations is potentially important in the phenomenon.